If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -5 = 4x + -2 Reorder the terms: -5 + 7x = 4x + -2 Reorder the terms: -5 + 7x = -2 + 4x Solving -5 + 7x = -2 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -5 + 7x + -4x = -2 + 4x + -4x Combine like terms: 7x + -4x = 3x -5 + 3x = -2 + 4x + -4x Combine like terms: 4x + -4x = 0 -5 + 3x = -2 + 0 -5 + 3x = -2 Add '5' to each side of the equation. -5 + 5 + 3x = -2 + 5 Combine like terms: -5 + 5 = 0 0 + 3x = -2 + 5 3x = -2 + 5 Combine like terms: -2 + 5 = 3 3x = 3 Divide each side by '3'. x = 1 Simplifying x = 1
| -45=-5x+10 | | 2(13-4x)-9(x+9)= | | 2/3n=-8/3 | | 9(-0,7b+3)-1.1=7 | | -10p^2+8=0 | | 0.04(y-7)+0.10y=0.18y-0.3 | | 3(-5)=-2b-7 | | 7y-4=6+2y | | -5(4-n)=-18+7n | | 12+p=10p-32 | | 3n+3=357 | | -40=8-6 | | 13z-4=-10 | | 3.15x-4.35=0.2x+2.57 | | X*2-2=x+64 | | 3c-4c=-4 | | G(x)=33x^2-9x-24 | | 4+2/3 | | 3(-5)=2nite | | X=0.95x+16 | | 5(4x-2)+9=16x+14 | | 0.75x-20=43 | | 14g+6=56 | | 4/5x-16=52 | | 48=.5x+10 | | (18x-9)/6 | | 2h+35=635 | | 4x+26=7x-13 | | -7c+1=43 | | 8(-4+7k)-4k=-84 | | -7y+5=-8y+6 | | v=x(23-2x)(11-2x) |